Control of Current Hysteresis of Networked Single‐Walled Carbon Nanotube Transistors by a Ferroelectric Polymer Gate Insulator. (9th October 2012) - Choi, Yeon Sik; Sung, Jinwoo; Kang, Seok Ju; Cho, Sung Hwan; Hwang, Ihn; Hwang, Sun Kak; Huh, June; Kim, Ho‐Cheol; Bauer, Siegfried; Park, Cheolmin
Abstract Films made of 2D networks of single‐walled carbon nanotubes (SWNTs) are one of the most promising active‐channel materials for field‐effect transistors (FETs) and have a variety of flexible electronic applications, ranging from biological and chemical sensors to high‐speed switching devices. Challenges, however, still remain due to the current hysteresis of SWNT‐containing FETs, which has hindered further development. A new and robust method to control the current hysteresis of a SWNT‐network FET is presented, which involves the non‐volatile polarization of a ferroelectric poly(vinylidene fluoride‐trifluoroethylene) (P(VDF‐TrFE)) gate insulator. A top‐gate FET with a solution‐processed SWNT‐network exhibits significant suppression of the hysteresis when the gate‐voltage sweep is greater than the coercive field of the ferroelectric polymer layer (≈50 MV m−1). These near‐hysteresis‐free characteristics are believed to be due to the characteristic hysteresis of the P(VDF‐TrFE), resulting from its non‐volatile polarization, which makes effective compensation for the current hysteresis of the SWNT‐network FETs. The onset voltage for hysteresis‐minimized operation is able to be tuned simply by controlling the thickness of the ferroelectric film, which opens the possibility of operating hysteresis‐free devices with gate voltages down to a few volts.